DNS blocking in PK: bbc.com, medium.com, nytimes.com, pornhub.com, signal.org +7 more (Pakistan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Pakistan. Data sourced from CensoredPlanet.
Censorship Incident ID: PK-2026-0011. Severity: critical. Confidence: 85%